Bleach. 42, Shock of the queen - Kubo, Tite (Kubo, Tite. Bleach (VIZ Media), 2012)
"The battle between the Soul Reaper captains and Aizen's Espadas continues with the fate of Karakura town hanging in the balance. And just as things take a turn for the worse, some surprising allies make their grand entrance."